Standarisasi Training untuk setiap Job Title di PT Ecogreen Oleochemicals Batam - Halim, Imanuel; Rahardjo, Jani (Jurnal Titra, 2013)
Ecogreen Oleochemicals Batam (EOB) Company is an oleochemical producing company which has been established since 1994. EOB Company has been providing a lot of trainings for each of their employee in order to improve the human resources quality, but the trainings given have not had a standard yet. At this time request for training filed by any user of departments and sections in the company and that make the resulted in training to be ovserlapping and not classifiable well. EOB Company has attempted to make a standard training by accommodating the organization needs, the job needs, and the personal needs, especially in Manufacturing Division. All of the requirement trainings that has been collected, was classified into three categories, which are basic training, development training, and additional training. The number of training which have Training Unit are 89 and divided based on six type of training. In the end, the result could bring benefits for the company, such as setting a standard training for the employees, making the training structure more systematic, and enabling the company to focus more on training needs for the employees.